ANALISIS COUNTRY OF ORIGIN TERHADAP PURCHASE DECISION MELALUI BRAND EQUITY SEBAGAI VARIABEL MEDIASI - Safuroh, Nyimas; Ramdan, Asep Muhamad; Jhoansyah , Dicky (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the effect of country of origin on purchase decision with brand equity as a mediating variable among Vivo smartphone users in Sukabumi City. The research employs a quantitative approach with a descriptive–causal method. A total of 195 respondents were selected using a probability sampling technique, and data were collected through a questionnaire measured using a semantic differential scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS) through SmartPLS 4, which includes evaluations of both the outer model and inner model. The results indicate that country of origin significantly influences brand equity, brand equity significantly influences purchase decision, and brand equity significantly mediates the relationship between country of origin and purchase decision. These findings suggest that consumers’ perceptions of a product’s country of origin affect their evaluation of the brand, which subsequently shapes their purchasing decisions. Strong brand equity enhances this relationship through increased brand awareness, perceived quality, positive brand associations, and consumer loyalty. This study contributes to the field of marketing by highlighting the mediating role of brand equity and providing strategic implications for companies seeking to strengthen brand value and improve product competitiveness.